2018
DOI: 10.1080/21515581.2018.1463229
|View full text |Cite
|
Sign up to set email alerts
|

Job insecurity, employee anxiety, and commitment: The moderating role of collective trust in management

Abstract: This article examines the moderating effect of collective trust in management on the relation between job insecurity (both objective and subjective) and employee outcomes (work-related anxiety and organisational commitment). This is contextualized in the modern British workplace which has seen increased employment insecurity and widespread cynicism. We use matched employer-employee data extracted from the British Workplace Employment Relations Survey (WERS) 2011, which includes over 16,000 employees from more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 57 publications
1
28
0
1
Order By: Relevance
“…This offers an insight on mechanism between the inconclusive relationship observed between MNCs, employment protection legislation and job deduction (Haaland et al, 2003;Wagner and Gelubcke, 2012) and is particular interest among developed economies where union memberships has declined in the last two decades (Jirjahn, 2017). This finding provokes the debate on the role of trade union when there is increased objective job insecurity (Angrave et al, 2017;Wang et al, 2018) and shed lights on the uprising union organizing carried out by workers in MNCs, such as Uber driver and Ryanair pilots strike (BBC news, 10 August 2018)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This offers an insight on mechanism between the inconclusive relationship observed between MNCs, employment protection legislation and job deduction (Haaland et al, 2003;Wagner and Gelubcke, 2012) and is particular interest among developed economies where union memberships has declined in the last two decades (Jirjahn, 2017). This finding provokes the debate on the role of trade union when there is increased objective job insecurity (Angrave et al, 2017;Wang et al, 2018) and shed lights on the uprising union organizing carried out by workers in MNCs, such as Uber driver and Ryanair pilots strike (BBC news, 10 August 2018)…”
Section: Discussionmentioning
confidence: 99%
“…As Hyman (2002:57) stated that "jobs are always at the mercy of economic and technological vagaries". Technological or external economic shocks may cost jobs, but there are a range of softer mechanisms firms have at their disposal, such as redeployment, pay freezes, temporary closures, and unpaid leave (Lai et al, 2016;Wang et al, 2018). Whether or not workers can constrain the imposition of compulsory redundancies is subject to their ability to mobilise countervailing power (Kelly, 2012;Olson, 2009).…”
Section: Trade Union and Job Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…4. Following Wang et al (2018) and Heaney et al (1994), job insecurity reflected the extent that employees feel their employment is secure (reversely coded as 1 = strongly agree; 5 = strongly disagree).…”
Section: Notesmentioning
confidence: 99%
“…Relationships based on trust tend to lead to harmonised workplaces which promote agency and cooperation. Indeed, management research has shown that trust is a crucial mediating factor in the smooth running of an organisation; from industrial relations to perceptions of job security and employee wellbeing (Lewicki, Elgoibar, and Euwema 2016;Wang, Mather, and Seifert 2018). However, given the increasing precariousness of the environment in which the Further Education (FE) sector operates, it is worth considering whether the benefits associated with building and maintaining trust in this context are problematic.…”
Section: Introductionmentioning
confidence: 99%